Cognitive Approach to Synonymic Relationship in Terminology - Khujakulov, Sunnatullo Anvar ugli (Universitas Muhammadiyah Sidoarjo, 2022)
The complex and least studied aspects of the study of terms include questions of their systemic organization at the level of lexico-semantic paradigmatics. An important problem that requires a detailed study on the material of various term systems is the implementation of the semantic process of synonymy in terminology. Based on this, the article reveals the content of the term